Business Model Canvas: Raffia Cutter 2 in 1 / Nur Namirah Mohd Zaki - Mohd Zaki, Nur Namirah (2020)
We target employees and users from the packaging industry. The industry such as textile industry has to do multiple tasks from the manufacturing to the packaging the textiles. The employees also need extra time to packaging the products which they have to measure and cut the raffia rope separately. This will lead to the delay of works. Next, this will also benefit the overall household, they can organize their stuff within the short time